Confirmation bias in innovation decision-making - Neto, J. C. (2022)
Potential innovators need to overcome many challenges. One such challenge is confirmation bias in decision-making. Human evolution has programmed the brain to act quickly in the face of a threat in the environment. In this way, thinking and (instantaneously) acting rationally is almost impossible for most people. This causes several negative effects on decision-making, notably cognitive biases. For example, an entrepreneur who wants to launch a new product on the market tends to convince herself/himself that her/his product is innovative, ignoring evidence to the contrary, this being a confirmation bias. An innovative analysis of the causes and consequences of the confirmation bias in innovation decision-making is the main goal of this article.